Too Subtle for Words: Doing Wordless Narrative Research - Jeff Horwat (Art/Research International, 2018)
Inspired by the wordless novels of early twentieth century Belgian artist Frans Masereel, this paper introduces wordless narrative research, a dynamic method of inquiry that uses visual storytelling to study, explore, and communicate personal narratives, cultural experiences, and emotional content too nuanced for language. While wordless narrative research can be useful for exploring a range of social phenomenon, it can be particularly valuable for exploring preverbal constructions of lived experiences, including trauma, repressed memories, and other forms of emotional knowledge often times only made accessible through affective or embodied modalities. This paper explores the epistemological claims of the method while describing five considerations for doing wordless narrative research. The paper concludes with a presentation of an excerpt of There is No (W)hole (Horwat, 2015), a surreal wordless autoethnographic allegory, as an example of wordless narrative research.